PENINGKATAN KESADARAN TENTANG KESEHATAN MASYARAKAT DI DESA PENE KECAMATAN JEROWARU MELALUI PROGRAM DESA SEHAT - Ramadhan, Fajri; Nurhidayah, Afifah; Jaelani, Ahmad; Hikmawati, Laepi; Purnamadani, Suci; Lestari, Silvia; Hidayat, Taufik; Tomberi, Lalu Hamdan Hasim; Hartika, Sasri Dinya; Pusvita, Lolita Yulis; Wirawan, Rahadi (Universitas Mataram, 2023)
Public health problems, especially in child development, are faced by many regions in Indonesia, including the province of West Nusa Tenggara. In recent years, a high rate of stunting has been identified in children. The Healthy Village Program is designed as part of student community service activities (KKN) as an effort to educate the public to minimize stunting rates in Pene village, Jerowaru District, East Lombok Regency. Program implementation is carried out through 2 types of approaches, namely counseling activities, and training or performance (demonstration). Counseling provided to the community includes counseling on stunting, early marriage and a clean and healthy lifestyle. While for training activities, namely training in making complementary food for ASI and performance in making a family medicinal plant garden (TOGA) and several other related activities. The activities that have been carried out have succeeded in encouraging the Pene village community to pay more attention to the growth and development of their children as an effort to prevent stunting, promote a clean and healthy lifestyle for the village community, and make young people aware of the potential problems that can arise as a result of early marriage. In addition, the family medicinal plant garden is used as an educational medium for school students and villagers in optimizing the use of residents' yards. The healthy village program which was carried out in this real work class has had a positive impact on the community, and supported the social program launched by the Pene village government.